Case report: Diagnosis and autogenous vaccine treatment of herpesvirus in a green turtle (Chelonia mydas) in Santa Marta, Colombia - Castro, Lyda R.; Villalba-Viscaíno, Vivian; Oviedo, Ángel; Zambrano, Edgar; Dávila, Angela; Naranjo, Gualberto; Oro-Genes, Blanca De; Combatt, Anthony; Prieto-Rodríguez, Julieth; Ortiz, Arnaldo; Villamizar, Natalia (Frontiers in Veterinary Science, 2024)
This study reports the first case of Fibropapillomatosis (FP) in the green turtle Chelonia mydas that has been successfully diagnosed and treated in Colombia. Worldwide, FP has reached epizootic proportions as it has been reported in marine turtles of tropical and subtropical waters, and in severe cases, it reduces the probability of survival. Treatment has been elusive as multiple surgical excisions are needed due to tumor recurrence. In this case, one green turtle with multiple tumors was diagnosed by histopathology and molecular detection of the Chelonid Herpesvirus 5 (ChHV5) by means of amplification and sequencing of the DNA polymerase (DNApol) gene. Two separate treatments that consisted of autogenous vaccines and surgical excisions were applied; the first one had a partial success as one out of the tumors treated reappeared after three months post-treatment. Treatment 2 consisted of an autogenous vaccine enriched with adjuvants and applied at increasing doses, after which, the tumor significatively decreased in size and was surgically removed. At the end of the six-month followup period, no tumor recurrence was observed, and the turtle was in apparent optimal health conditions. These findings, although limited, suggest a possible treatment that might help to contain this epizootic problem.